Colonoscopic and Histopathological Findings in Patients with Various Lower Gastrointestinal Symptoms: An Experience in Tertiary Care Centre of Pakistan - Aliya Farooq Raja; Siddiqi, Fuad Ahmad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency of various lower GI diseases and their associated colonoscopic findings and to emphasize the value of colonoscopy and biopsy in the diagnosis of lower GI pathologies. Study Design: Prospective longitudinal study Place and Duration of Study: Department of Gastroenterology, Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Oct 2023 to May 2024. Methodology: A total of 452 patients between the age of 19 - 67 who underwent colonoscopy were enrolled in the study. Their presenting complaints were documented and its correlation with colonoscopic findings was assessed. Histopathological results were also sought by contacting the participants via phone. Results: The results revealed that chronic diarrhea and bleeding per rectum were the frequently encountered symptoms in our setup followed by anemia, weight loss and constipation. Male were affected more than female. Inflammatory bowel disease (IBD) came out to be a major cause in patients with chronic diarrhea and bleeding per rectum (50% and 42% respectively). Colonic growths were commonly seen in patients with anemia, weight loss and constipation; biopsy of which mostly showed adenocarcinoma. Conclusion: Colonoscopy is helpful in establishing association between common GI symptoms and their colonoscopic findings and also play beneficial role in early diagnosis and timely management of major diseases of lower GI tract.